2019
DOI: 10.1038/s41598-019-51172-2
|View full text |Cite|
|
Sign up to set email alerts
|

Risk factors for serious morbidity, prolonged length of stay and hospital readmission after laparoscopic appendectomy - results from Pol-LA (Polish Laparoscopic Appendectomy) multicenter large cohort study

Abstract: <50 3269 (70.79%) First operator, n (%) Specialist 2589 (56.06%) Resident 2029 (43.94%) Median operative time, min (IQR) 55 (40-70) Technique, n (%) Clipping 2841 (61.64%) Suturing/ligature 453 (9.79%) Stapler 313 (6.75%) Endoloop 606 (13.11%) Röder loop 403 (8.71%) Complicated appendicitis, n (%) 1269 (27.48%) Uncomplicated appendicitis, n (%) 3349 (72.52%) Intraoperative adverse events, n (%) 104 (2.25%) Drainage, n (%) 3493 (75.64%) Postoperative morbidity, n (%) 310 (6.71%) Clavien-Dindo classification of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
24
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 38 publications
14
24
2
1
Order By: Relevance
“…These reasons also prolong the hospitalization period of the patients. In this study, it was also reported that the hospital stay was longer in the CA group, which is consistent with the previous studies [ 19 , 20 ].…”
Section: Discussionsupporting
confidence: 93%
“…These reasons also prolong the hospitalization period of the patients. In this study, it was also reported that the hospital stay was longer in the CA group, which is consistent with the previous studies [ 19 , 20 ].…”
Section: Discussionsupporting
confidence: 93%
“…A multicentered large cohort study in Poland also showed that appendicitis (through the Alvarado score) has a significant relationship with the length of stay (OR, 1.10; p =0.008). Similar relations to the length of stay were also found on symptom onset before the surgery (OR, 1.72; p <0.001), diabetes (OR, 3.96; p <0.001), and old age (OR, 2.78; p <0.001) [ 34 ].…”
Section: Discussionmentioning
confidence: 53%
“…It is worth mentioning that some researchers have also focused on the impact of LOS on readmission. For example, in the study of laparoscopic appendectomy, a prolonged LOS is an influencing factor of postoperative adverse events such as readmission and clinical endpoints (Walędziak et al, 2019). The proportion of patients readmitted to the ICU within 30 days would, in turn, affect the LOS (Long & Mathews, 2018).…”
Section: Results Of the Hfs-lightgbmmentioning
confidence: 99%